Is the uptake, engagement, and effectiveness of exclusively mobile interventions for the promotion of weight‐related behaviors equal for all? A systematic review. (9th January 2023) - Szinay, Dorothy; Forbes, Cynthia C.; Busse, Heide; DeSmet, Ann; Smit, Eline S.; König, Laura M.
Summary: Mobile health interventions are promising behavior change tools. However, there is a concern that they may benefit some populations less than others and thus widen inequalities in health. This systematic review investigated differences in uptake of, engagement with, and effectiveness of mobile interventions for weight‐related behaviors (i.e., diet, physical activity, and sedentary behavior) based on a range of inequality indicators including age, gender, race/ethnicity, and socioeconomic status. The protocol was registered on PROSPERO (CRD42020192473). Six databases (CINAHL, EMBASE, ProQuest, PsycINFO, Pubmed, and Web of Science) were searched from inception to July 2021. Publications were eligible for inclusion if they reported the results of an exclusively mobile intervention and examined outcomes by at least one inequality indicator. Sixteen publications reporting on 13 studies were included with most reporting on multiple behaviors and inequality indicators. Uptake was investigated in one study with no differences reported by the inequality indicators studied. Studies investigating engagement ( n = 7) reported differences by age ( n = 1), gender ( n = 3), ethnicity ( n = 2), and education ( n = 2), while those investigating effectiveness ( n = 9) reported differences by age ( n = 3), gender ( n = 5), education ( n = 2), occupation ( n = 1), and geographical location ( n = 1). Given the limited number of studies and their inconsistent findings, evidence of the presence of a digital divide in mobile interventions targeting weight‐related behaviors is inconclusive. Therefore, we recommend that inequality indicators are specifically addressed, analyzed, and reported when evaluating mobile interventions.